The natural science practical guide developed based on critical thinking skills: Implementation test results - Dewi Susanti; Muhammad Zaini; Aminuddin Prahatama Putra (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
The expected learning outcomes in the 21st century are that students have critical thinking skills. The critical thinking skills are an important requirement to solving problems in life. The material in the Natural Science subject needs to be understood by relying on critical thinking skills, and is relevant to the environment. However, SMP Negeri 1 Hulu Sungai Tengah has not been equipped with an optimal learning guide to meet these demands, so a science practicum guide based on critical thinking skills has been developed. This study aims to test the practicality and effectiveness of the developed science practicum guide. Practicality is obtained from student response questionnaires and observations of the implementation of the use of practicum guides, while effectiveness is obtained from the categorization of the N-Gain Test of students' critical thinking skills. The results show: a practical science practicum guide developed with one-to-one evaluation results 97.22% (very good), student responses of 98.57% (positive), and 100% (very good) implementation; and effective with the results of the N-Gain categorization of students' critical thinking skills high for three indicators, and moderate for two indicators.Abstrak Hasil belajar yang diharapkan di abad 21 adalah peserta didik memiliki keterampilan berpikir kritis. Keterampilan berpikir kritis merupakan syarat penting untuk memecahkan masalah dalam kehidupan. Materi dalam mata pelajaran Ilmu Pengetahuan Alam perlu dipahami dengan mengandalkan keterampilan berpikir kritis, dan relevan dengan lingkungan hidup. Namun, di SMP Negeri 1 Hulu Sungai Tengah belum dilengkapi dengan panduan belajar yang optimal dalam memenuhi tuntutan tersebut, sehingga dikembangkan panduan praktikum IPA berbasis keterampilan berpikir kritis. Penelitian ini bertujuan menguji kepraktisan dan keefektivan dari panduan praktikum IPA yang dikembangkan. Kepraktisan diperoleh dari angket respon peserta didik dan observasi keterlaksanaan penggunaan panduan praktikum, sedangkan keefektifan diperoleh dari kategorisasi Uji N-Gain keterampilan berpikir kritis peserta didik. Hasilnya menunjukkan: panduan praktikum IPA yang dikembangkan praktis dengan hasi uji perorangan 97,22% (sangat baik), hasil respon peserta didik 98,57% (positif), dan keterlaksanaan 100% (sangat baik). dan efektif dengan hasil kategorisasi N-Gain keterampilan berpikir kritis peserta didik tinggi untuk tiga indikator, dan sedang untuk dua indikator.